PENGARUH E-FILLING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI ATAS PELAPORAN SURAT PEMBERITAHUAN TAHUNAN PADA KPP PRATAMA KISARAN - Prianda Pebri (MANAJEMEN DEWANTARA, 2020)
his study aims to determine the effect of the Implementation of the EFilling System on Taxpayer Compliance with Annual Tax Reporting in the KPP Primary Range. The data of this study were obtained from a questionnaire (Primary) distributed to taxpayers registered in the KPP Pratama Kisaran using the incidental sampling method. The population of this research is the individual taxpayer who is registered as the e-filling taxpayer in the KPP Pratama Kisaran. The sample used in this study were 100 respondents. The questionnaire was tested for validity and reliability before the study. The prerequisite tests used were normality test and homogeneity test. Hypothesis testing used is simple linear regression and Moderated Regression Analysis. This research was proven through a simple regression analysis that obtained an R Square value of 0.368, which can be interpreted that the magnitude of the effect of the E-Filling System Implementation on Taxpayer Compliance was 36.8%. The results of the t-statistic test produced a significance value smaller than the level of significant at 0,000 <0.05. So the results of this study indicate that the adoption of the E-Filling System has a positive and significant effect on Taxpayer Compliance with Annual SPT Reporting.Keywords: E-Filling, Kepatuhan Wajib Pajak